The archaeological direction in Japanese studies in Russia: Development, peculiarities, personal experience - A. V. Tabarev (Японские исследования)
The archaeological direction in the Japanese studies in Russia originated at the end of the 19th century on the basis of the first trips and acquaintance with the antiquities of Japan (M.I. Venyukov, A.V. Grigoriev, I.S. Polyakov, D.M. Pozdneev), and transformed into an original direction in the Soviet period. The fruitful dialogue between Russian and Japanese archaeologists is largely due to both the territorial proximity and common roots of ancient cultures, starting from the Stone Age, as well as mutual interest in the archaeology of the Pacific basin as a whole. Since the early 1960s, one of the leading roles in this collaboration is played by the Novosibirsk Scientific Center (Institute of History, Philology and Philosophy, Siberian Branch of the Academy of Sciences of the USSR, Faculty of Humanities of NSU) and such specialists as A.P. Okladnikov, A.P. Derevyanko, R.S. Vasilevsky, and V.E. Larichev. In the first post-Soviet decade, there was a transition to new formats – long-term joint projects and archaeological expeditions, which are carried out on the basis of bilateral agreements between research organizations in Japan and Russian institutes (universities, museums) from a number of cities in Siberia and the Russian Far East. Cooperation reached its peak in 2007/8–2019, enjoying the support of Russian (RSFH, RFBR, RSF) and Japanese scientific foundations, and was implemented in a variety of formats (projects, exchanges, internships, symposiums, exhibitions, publications, etc.) and in a variety of geographical areas, both in Russia and Japan, as well as third countries – in Central Asia (Mongolia) and South America (Ecuador). One of the striking examples of such interaction is the fruitful cooperation of the Division of Foreign Archaeology (Institute of Archaeology and Ethnography SB RAS, Novosibirsk) and the Laboratory of Archaeology (Tohoku University, Sendai), resulting in a large number of publications in leading scientific journals and several dissertation studies on the Jomon and Kofun periods.